This is what the US leading indicators lead - Maximo Camacho; Gabriel Pérez Quirós (European Central Bank (ECB), 2000)
We propose an optimal filter to transform the Conference Board Composite Leading Index (CLI) into recession probabilities in the US economy. We also analyze the CLI's accuracy at anticipating US output growth. We compare the predictive performance of linear, VAR extensions of smooth transition regression and switching regimes, probit, nonparametric models and conclude that a combination of the switching regimes and nonparametric forecasts is the best strategy at predicting both the NBER business cycle schedule and GDP growth. This confirms the usefulness of CLI, even in a real-time analysis.
Keywords: C32; C53; 330; leading indicators; optimal forecasting rule; turning points